Data Hiding and Its Applications Digital Watermarking and Steganography - Megías, David; Mazurczyk, Wojciech; Kuribayashi, Minoru (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Data hiding techniques have been widely used to provide copyright protection, data integrity, covert communication, non-repudiation, and authentication, among other applications. In the context of the increased dissemination and distribution of multimedia content over the internet, data hiding methods, such as digital watermarking and steganography, are becoming increasingly relevant in providing multimedia security. The goal of this book is to focus on the improvement of data hiding algorithms and their different applications (both traditional and emerging), bringing together researchers and practitioners from different research fields, including data hiding, signal processing, cryptography, and information theory, among others.